Distribution and Influencing Factors of the Sialic Acid Content in the Breast Milk of Preterm Mothers at Different Stages - Chen, Zekun; Chang, Yanmei; Liu, Hui; You, Yanxia; Liu, Yanpin; Yu, Xue; Dou, Yuqi; Ma, Defu; Chen, Lijun; Tong, Xiaomei; Xing, Yan (Frontiers in Nutrition, 2022)
Background & Aims: This study aims to detect breast milk sialic acid (SA) content and the change rule, understand each stage breastfeeding SA secretion and the influence factors of the human milk SA content. Methods: We recruited mothers and their infants as our subjects. At day 7, 14, 30, 120 and 365 after delivery, the contents of SA in breast milk were collected and detected through Fluorescence Detector-High Performance Liquid Chromatography. The participants completed baseline questionnaire at ≤day7 and were followed up at day 30, 120 and 365. Results: A total of 95 mothers with 122 infants were included in the analysis, including 22 mothers with 22 term infants, 25 mothers with 35 late preterm infants, 31 mothers with 39 very preterm infants, and 17 mothers with 26 extremely preterm infants. The results of study showed that, compared with breast milk of term mothers at the same period, breast milk of preterm mothers contained more SA at each time node, and the content of SA in breast milk increased with decreasing gestational weeks. Moreover, maternal age, pre-pregnancy BMI, and delivery mode had significant effects on total SA in breast milk especially for the preterm infant breast milk. Significant negative associations occurred between SA contents and infant growth status, especially in preterm infants. Conclusions: With the prolongation of lactation time, the content of SA in breast milk gradually decreased, and the content of SA in the breast milk of preterm mothers was higher than that of term mothers. In addition, SA content was associated with maternal age, pre-pregnancy BMI, and delivery mode. Moreover, high levels of SA in breast milk were useful for the catch-up growth of preterm infants.